2001
DOI: 10.1122/1.1392295
|View full text |Cite
|
Sign up to set email alerts
|

The effects of interparticle interactions and particle size on reversible shear thickening: Hard-sphere colloidal dispersions

Abstract: A comparison between the effects of two colloidal stabilizing methods ͑electrostatic versus Brownian͒ on the reversible shear thickening transition in concentrated colloidal suspensions is explored. Five suspensions of monodisperse silica are synthesized via the Stöber synthesis and dispersed in an index matched organic solvent to minimize van der Waals interactions. The residual surface charge is neutralized with nitric acid (c HNO 3 Ϸ 0.1 M͒ resulting in a near hard-sphere interaction that is confirmed by sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
156
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 279 publications
(172 citation statements)
references
References 51 publications
15
156
0
1
Order By: Relevance
“…Also, the deformation or crack of the hard-sphere particles as well as the volume compressibility of the particles and the polyethylene glycol could be neglected. In addition, the previous studies 8,19,[27][28][29][30] showed that critical conditions were required to occur the shear thickening in STF. A minimum strain might be not obtained in several tens of nanoseconds to occur the shear thickening behavior when the particle velocity decays to a relative low value, leading to the saturations of the stress attenuation and the energy absorption in the STF.…”
mentioning
confidence: 94%
“…Also, the deformation or crack of the hard-sphere particles as well as the volume compressibility of the particles and the polyethylene glycol could be neglected. In addition, the previous studies 8,19,[27][28][29][30] showed that critical conditions were required to occur the shear thickening in STF. A minimum strain might be not obtained in several tens of nanoseconds to occur the shear thickening behavior when the particle velocity decays to a relative low value, leading to the saturations of the stress attenuation and the energy absorption in the STF.…”
mentioning
confidence: 94%
“…Such interactions could greatly influence the flow behaviour, as they do in strongly aggregating colloids at lower densities 10 . The fundamental physics of colloidal jamming is therefore better addressed in model systems of nearly hard-sphere particles [3][4][5][6] , which are forced into contact by external stresses without the added complexities of ill-defined interactions.…”
mentioning
confidence: 99%
“…Included in this study are fabrics treated with STFs. STFs are materials that are flowable at low stress levels but transition to a solid-like state when subjected to higher stresses (1)(2). Previous experiments have shown that adding STFs to high performance fabrics such as nylon and Kevlar * can increase the protective properties of these fabrics, especially against puncturing threats (3-6).…”
Section: Shear Thickening Fluid (Stf)-treated Fabricsmentioning
confidence: 99%